1995
DOI: 10.1136/thx.50.7.758
|View full text |Cite
|
Sign up to set email alerts
|

Changes in symptoms, peak expiratory flow, and sputum flora during treatment with antibiotics of exacerbations in patients with chronic obstructive pulmonary disease in general practice.

Abstract: Background -Bacterial infections of the lower airways during an exacerbation in patients with asthma or chronic obstructive pulmonary disease (COPD) may be the cause of an exacerbation or the consequence of a viral infection or an increase in airways limitation. To determine whether bacterial infection is an important component in the pathogenesis of an exacerbation, the effects of antimicrobial treatment must be studied. Methods -Patients with asthma or COPD seen in general practice were studied in a double b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 28 publications
1
51
0
6
Order By: Relevance
“…The results of our study indicated that this type of relationship could only be applied to CRP level, but not to leukocyte count. These results are consistent with previously reported results [30][31][32] . Lower values of the mMRC dyspnea scale are associated with better spirometry and blood gas analysis results in COPD.…”
Section: Discussionsupporting
confidence: 83%
“…The results of our study indicated that this type of relationship could only be applied to CRP level, but not to leukocyte count. These results are consistent with previously reported results [30][31][32] . Lower values of the mMRC dyspnea scale are associated with better spirometry and blood gas analysis results in COPD.…”
Section: Discussionsupporting
confidence: 83%
“…This conclusion and the fact that papers in these meta-analyses included both in-and outpatients, makes it uncertain as to whether antibiotic treatment in exacerbations in all primary care patients is useful. The two studies carried out in primary care failed to show relevant effects [30,31]. However, data on patients with severe exacerbations and exacerbations of mild and severe COPD in primary care were lacking.…”
Section: What Are the Indications For Antibiotic Treatment Of Exacerbmentioning
confidence: 99%
“…At present, however, there is no such need. Firstly, the effect of antimicrobial treatment in acute exacerbations is probably confined to the subgroup of patients with ANTHONISEN et al [20] type-1 exacerbations and those with defined risk factors according to BALL et al [23] and other studies (cardiopulmonary comorbidity and frequent hospitalizations) [12,20,24,25]. Even then, the cure rate using placebo is high.…”
Section: S Ewigmentioning
confidence: 99%